THE ROLE OF FOLATE, VITAMIN B12 AND B6 IN HYPERHOMOCYSTEINEMIA AS THE RISK FACTOR OF CARDIOVASCULAR DISEASE: NARRATIVE REVIEW - Semme, Muhammad Yatsrib; Salam, Muhammad Rheza Rivaldi; Budiamin, Fadhlan Auliah (Universitas Tadulako, 2024)
Cardiovascular disease (CVD), encompassing ailments affecting the heart and vascular system, is estimated to contribute to one-third of global mortality, and its prevalence is continuously rising. The etiology of this condition is multifactorial, making it challenging to identify a singular causative factor. Homocysteine, a factor identified in the 1990s, is known to contribute to the development of atherosclerotic vascular disease and hypercoagulability. Although there is a definite connection, the assessment and management of this condition are still a subject of debate due to inconsistent research findings on its impact in lowering the risk of cardiovascular disease. B vitamins are a collection of chemical compounds that play a crucial role in physiological function. However, the body does not produce them naturally and they need to be obtained from dietary intake. Vitamins B6, B9, and B12 are crucial in the metabolism of homocysteine. The cause of hyperhomocysteinemia is believed to be a deficiency of certain vitamins, particularly folate, B12, and B6, which are important for effectively recycling homocysteine in the methionine cycle. Vitamin B is intricately linked to both the homocysteine and cardiovascular disease (CVD) pathways.